Intangibles : management, measurement, and reporting - Lev, Baruch (Brookings Institution Press, 2001)
Annotation This book is the first comprehensive, scientifically based study of the nature and impact of intangibles. Weaving case studies and real-world examples with contemporary business theory, Baruch Lev - establishes an economic framework to analyze managerial and investment issues concerning intangibles; - surveys the impact of intangibles on corporate performance and market values, including management difficulties, risk, questions of property rights, marketability, and cost structure; - analyzes information deficiencies associated with intangibles, including the major economic principles governing intangible investments, limits of management information systems, and recommendations for improved accounting disclosure; - sets forth a comprehensive information system -- aimed at satisfying the needs of both internal and external decision makers -- to reflect the impact and value of intangibles within the context of enterprise performance.